Crystal structure and chemistry of natural kutinaite from Černý Důl, Krkonoše, Czech Republic. (2nd January 2018) - Bindi, Luca; Makovicky, Emil
Abstract: We have characterized the crystal structure of natural kutinaite, a rare mineral from the ores of Černý Důl, Czech Republic, by single-crystal X-ray diffraction and chemical analysis. We found that the structure of natural kutinaite is not identical to that of synthetic Cu14 Ag6 As7, previously reported to be cubic, space group Pm 3 m . Although topologically similar, the structure of natural kutinaite is indeed tetragonal, space group P 4/ mmm, with cell parameters: a = 11.789(2), c = 11.766(2) Å, V = 1635.5(4) Å 3 and Z = 4. Electron microprobe analyses pointed to the (K, Tl)0.25 Cu14 Ag6 As6.75 stoichiometry ( Z = 4), or (K, Tl)Cu56 Ag24 As27 with Z = 16. The crystal structure of an untwinned crystal has been refined to R 1 = 2.61%. It consists of clusters of eight edge-sharing tetrahedra of Cu, which alternate in a 3D chess-board manner with octahedral clusters of six Ag atoms. The latter are surrounded by triangularly coordinated copper in eight faces of a cuboctahedron. The last structure components are large cavities containing partly occupied (K, Tl) sites, coordinated by 18 Ag and As ligands. The structure is full of direct metal-metal contacts although As plays the role of anion, associating especially with copper.